Memerdekakan Belajar Mahasiswa Melalui Kemampuan Berpikir Kreatif Berbasis Pendekatan Heutagogy - Berta Apriza; Yasinta Mahendra; Rohmani Rohmani (Journal of Psychology and Instruction, 2024)
The Kampus Merdeka program presents challenges and opportunities for students to develop creativity, capacity, personality, and independence in seeking and discovering knowledge through real-world dynamics. This program allows students to engage more actively in a self-directed and flexible learning process tailored to their needs and interests. This study aims to describe how to liberate PGSD students' learning through creative thinking skills using a heutagogical approach. This approach emphasizes student-centered learning, where students are encouraged to take full responsibility for their own learning process. The research employed a descriptive quantitative approach with the subjects being fourth-semester PGSD students from class B at Universitas Muhammadiyah Kotabumi. Data was collected through questionnaires to measure creative thinking indicators such as curiosity, imagination, originality, the ability to ask questions, unique ideas, freedom of expression, and alternative solutions. The results showed that 14% of students demonstrated curiosity and imagination, 16% originality and the ability to ask questions, 13% unique ideas, 17% freedom of expression, and 10% alternative solutions. The conclusion of this study is that students tend to demonstrate freedom of expression as the primary indicator of creative thinking. The implications of this research highlight the need to apply a heutagogical approach in learning to further promote the development of students' creative thinking abilities.